PHYSICAL-MECHANICAL PROPERTIES OF INTERPOLYMER COMPLEX FILM BASED ON SODIUM CARBOXYMETHYL CELLULOSE AND POLYACRYLAMIDE - Zhorakulov , Sanjar Zafarjon o‘g‘li (Educational Research in Universal Sciences, 2023)
Innovative developments serve the integration of science and production. Uzbekistan, which has a highly developed production and processing industry, has a large amount of resources for obtaining new polymer materials of great practical importance. This brings not only the production of valuable products, but also the study of their processing technologies to the level of today’s urgent issue.